The choice between arm's-length and relationship debt: Evidence from eLoans - Sumit Agarwal; Robert Hauswald (Federal Reserve Bank of Chicago, 2008)
Using a unique sample of comparable online and in-person loan transactions, we study the determinants of arm's-length and inside lending focusing on the differential information content across debt types. We find that soft private information primarily underlies relationship lending whereas hard public information drives arm's-length debt. The bank's relative reliance on public or private information in lending decisions then determines trade-offs between the availability and pricing of credit across loan types. Consistent with economic theory, relationship debt leads to informational capture and higher interest rates but is more readily available whereas the opposite holds true for transactional debt. In their choice of loan type, lender switching, and default behavior firms, however, anticipate the inside bank's strategic use of information and act accordingly.
Keywords: G21; L11; L14; D44; 330